Systematization of nursing care from the perspective of students: a phenomenological approach (Research, Society and Development, 2022)
Objective: To analyze the facilities as well as the difficulties of the Systematization of Nursing Care from the perspective of students in the last year of the Graduation Course in Nursing at a Private University in the south of Minas Gerais. Method: Descriptive study with a qualitative approach, following Phenomenology. The scenario consists of a Private Higher Education Institution, in which 26 students who were attending the last year of the Nursing Graduation took part. Data collection was performed through semi-structured interviews and data analysis occurred through inductive analysis. Results: After analyzing the data, the students' knowledge about the Systematization of Nursing Care and the Nursing Process was evident, with numerous facilities as well as difficulties related to learning and implementing these tools. Conclusions: The students understand the meaning of the Systematization of Nursing Care, however, some difficulties are still clear that require greater attention from the training centers so that learning is carried out more proficiently.